Green intellectual capital / Salwa Muda, Musliha Musman and Raziah Bi Mohamed Sadique - Muda, Salwa; Mohamed Sadique, Raziah Bi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Intellectual capital encompasses all the processes and the assets which are not normally shown on the balance sheet, including the intangible assets in modern accounting such as trademarks and patents (Edvinsson, 1997). These intangible assets and resources that are categorized into human capital, structural capital and relational capital are believed to drive value creation of the organisations by improving operational efficiency, fostering innovation and enhancing performance. Building on the concept of intellectual capital, green intellectual capital (GIC) is a relatively modern evolution emphasizing on blending intangible assets and a commitment to environmental awareness. As Industry 4.0 advances with digitization and automation, organizations are increasingly recognizing their environmental responsibilities and the urgent need to reduce carbon emissions, driving a shift towards sustainable practices. Embracing green intellectual capital (GIC) and aligning with the United Nations' Sustainable Development Goals (SDGs) are key strategies for achieving environmental sustainability (Soomro & Soomro, 2024). Below is the definition of GIC and its dimensions.